Insights on the utilisation of tissue culture to aid new breeding techniques for cowpea (Vigna unguiculata L.) improvement - Vacu, Malizukiswe Vincent; Nzama, Promise Sifiso; Adegbaju, Muyiwa Seyi (Frontiers in Horticulture, 2025)
Cowpea (Vigna unguiculata L.) is an underutilised vegetable legume indigenous to and predominantly cultivated and consumed in Africa. However, its reach in agricultural production and consumption has expanded globally. This resilient crop is known for its ability to withstand various environmental stressors, making it suitable for marginal crop production systems commonly used by small-scale farmers. Although cowpea exhibits tolerance to drought, it is notably sensitive to salinity stress and biotic agents. The degree of tolerance to drought varies among different cultivars, which requires further research to develop more resilient varieties.The changing climate patterns and associated uncertainties highlight the urgent need to breed more resilient and productive cowpea cultivars. Conventional plant breeding techniques have produced new varieties of cowpeas, yet the limited genetic diversity within cultivated cowpeas poses challenges for future conventional breeding efforts. New breeding techniques (NBTs), including gene editing tools, single base pair alterations, and DNA methylation methods, offer promising alternatives to accelerate cowpea improvement. However, such approaches are also faced with challenges associated with the success of organogenesis (OG) and somatic embryogenesis (SE) in tissue culture. This review examines challenges and advances in the use of tissue culture to enhance cowpea productivity and resilience against abiotic and biotic stresses.